Extraction optimization of polyphenols from organic tea leaves (Camellia sinensis) - Sim, Zeh Shing (2014)
Tea (Camellia sinensis) is the most widely consumed beverage in the world next to water. Tea exhibits medicinal properties such as scavenger of free radicals, cancer prevention, antimutagenic activity and coronary diseases prevention. The beneficial of the tea is related to its phenolic contents. This study was to optimize the polyphenols extraction from an organic tea sample (T01) collected from Sabah Tea Plantation, Ranau. Extraction conditions studied included the effects of ethanol concentration (50% – 95%), extraction period (three hours – 24 hours), extraction temperature (~25 °C – 50 °C) and shaking at 120 rpm. The total polyphenols content (TPC) was determined by using Folin-Ciocalteu method while the antioxidative property was determined using 1, 1–diphenyl–2–picrylhydrazyl (DPPH). Two standards commonly present in tea, namely (+)–catechin (C) and (– )–epigallocatechin–3–gallate (EGCG) were used for qualitative and quantitative analyses using reverse phase high performance liquid chromatography (RP-HPLC). In this study, all the extraction conditions were found to pose significant effect (p < 0.05) on the TPC recovered. TPC was the highest by using 70% ethanol, 12 hours extraction period and 40 °C with shaking. Through response surface method (RSM), the optimal extraction conditions to recover the most TPC were concluded to be 65% ethanol, 12 hours extraction and 35 °C with shaking. The amount of recovered TPC under optimized conditions was 592.33 mg GAE/g, inhibition of 88.11% DPPH, (+)–catechin of 14.21 mg/g and EGCG of 318.09 mg/g. The TPC was also found to be positively correlated (r = 0.890, p < 0.01) with antioxidative property. This study has determined an optimized extraction conditions to efficiently recover TPC from organic tea leaves. The TPC recovered contains polyphenols which have been linked to the antioxidative property. This study provides useful information for further studies especially in scaling up the TPC extraction for commercial purposes.